HIV seroconversion among female sex workers: retrospective cohort study from a large-scale HIV prevention and sexual and reproductive health program in Tanzania - Mbita, Gaspar; Mwanamsangu, Amasha; Komba, Albert N.; Casalini, Caterina; Luponya, Maneno; Curran, Kelly; Christensen, Alice; Kim, Young-Mi; Reed, Jason; Makyao, Neema; Kategile, Upendo; Conserve, Donaldson F.; et al. (Frontiers in Reproductive Health, 2024)
Introduction: In 2016, UNAIDS set ambitious targets to reduce global HIV infections by 75% by 2020 and 90% by 2030, based on the 2.1 million new infections reported in 2010. However, by 2022, new HIV infections had only decreased by 38%, from 2.1 million in 2010 to 1.3 million in 2022, raising concerns about reaching the 2030 goal. Female sex workers (FSWs) in sub-Saharan Africa face a disproportionately high risk of HIV acquisition, contributing 5-20% of all new infections in several countries in the region. This analysis investigates HIV seroconversion and associated factors among FSWs, offering insights into critical interventions for preventing HIV transmission in this population and advancing the goal of ending the HIV pandemic by 2030. Methods: We conducted a retrospective cohort study involving 17,977 FSWs who initially tested HIV negative upon enrollment in the Sauti project between October 2016 and September 2018. HIV incidence rates were calculated by dividing the number of new HIV cases by observed person-time within the cohort. Cox regression analysis identified factors associated with seroconversion. Results: The study revealed an HIV incidence rate of 8.6 per 100 person-years among FSWs (95% confidence interval [CI]: 8.1-9.1). Factors independently associated with HIV seroconversion included age 35 years or older (adjusted hazard ratio [aHR]: 2.53; 95% CI: 2.03-3.14), unprotected sex (aHR: 1.27; 95% CI: 1.13-1.42), STI symptoms (aHR: 1.99; 95% CI: 1.67-2.38), and alcohol consumption before sex (aHR: 1.20; 95% CI: 1.07-1.34). Conclusion: Targeted interventions are vital in curbing HIV transmission among FSWs, with a focus on expanding access to primary HIV prevention services, particularly for older FSWs who face heightened risk. Tailored sexual health education programs are imperative to encourage consistent condom use and enable informed decision-making. Accessible and timely STI screening and treatment services are crucial to mitigate HIV transmission risk. Collaborative partnerships between healthcare providers, community organizations, and government agencies are essential in implementing these interventions among FSWs.